2012
DOI: 10.4161/cib.18761
|View full text |Cite
|
Sign up to set email alerts
|

The post-mitotic state in neurons correlates with a stable nuclear higher-order structure

Abstract: Neurons become terminally differentiated (TD) post-mitotic cells very early during development yet they may remain alive and functional for decades. TD neurons preserve the molecular machinery necessary for DNA synthesis that may be reactivated by different stimuli but they never complete a successful mitosis. The non-reversible nature of the post-mitotic state in neurons suggests a non-genetic basis for it since no set of mutations has been able to revert it. Comparative studies of the nuclear higher-order st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 70 publications
(97 reference statements)
1
17
0
1
Order By: Relevance
“…This classical observation has stood the test of time [Woodcock and Ghosh, 2010]. In the present study, we confirm and further expand the previous evidence that the NHOS, defined by the set of structural interactions between nuclear DNA and the NM, is cell-type specific [Rivera-Mulia and Aranda-Anzaldo, 2010; Trevilla-Garc ıa and Aranda- Anzaldo, , 2012. Here, we show that the NHOS of neurons is clearly different at the large-scale from that in hepatocytes (as reflected by the significant difference in the average DNA loop size, Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This classical observation has stood the test of time [Woodcock and Ghosh, 2010]. In the present study, we confirm and further expand the previous evidence that the NHOS, defined by the set of structural interactions between nuclear DNA and the NM, is cell-type specific [Rivera-Mulia and Aranda-Anzaldo, 2010; Trevilla-Garc ıa and Aranda- Anzaldo, , 2012. Here, we show that the NHOS of neurons is clearly different at the large-scale from that in hepatocytes (as reflected by the significant difference in the average DNA loop size, Fig.…”
Section: Discussionsupporting
confidence: 90%
“…So far, the evidence indicates that the NHOS is cell‐type specific at the local and at the large‐scale level [Rivera‐Mulia and Aranda‐Anzaldo, ; Trevilla‐García and Aranda‐Anzaldo, , ]. Thus, it has been suggested that the NHOS is rather independent of functional constraints related to replication and/or transcription and that it is primarily established following structural and thermodynamic constraints that impinge on chromosomal DNA and the NM [Aranda‐Anzaldo, , ]. This suggestion is consistent with recent evidence that the NHOS is not conserved between similar cell types from closely related species [Silva‐Santiago et al, ].…”
mentioning
confidence: 99%
“…EDTP/MTMR14 has two main functions: negative regulation of autophagy and disease-causing effect if deficient in the muscles [1,[11][12][13][14][15]. Drosophila EDTP has two peaks of expression, one Motoneurons are highly specialized and terminally differentiated with reduced function of global genome repair [32,33]. More importantly, neuronal cells utilize autophagy as an essential process for normal turnover of cytoplasmic contents [34].…”
Section: Discussionmentioning
confidence: 99%
“…4). Because heavy metal toxicity in PSP preferentially affects neurons 29 , which are non-dividing post-mitotic cells 30 , we compared the sensitivity of SH-SY5Y cells to heavy metals in both non-differentiated and neuron-like differentiated states.…”
Section: Chromium and Nickel Induced Cell Death In Cycling And Terminmentioning
confidence: 99%